Sustainable evaluation and verification in supply chains: Aligning and leveraging accountability to stakeholders - Gualandris, Jury; Klassen, Robert D.; Vachon, Stephan; Kalchschmidt, Matteo (Journal of Operations Management, 2015)
AbstractManagers are being challenged by multiple (and diverse) stakeholders, which have variety of expectations and informational needs about their firm’s supply chains. Collectively, these expectations and needs form a multi‐faceted view of stakeholder accountability, namely the extent to which a firm justifies behaviors and actions across its extended supply chain to stakeholders. To date, sustainable supply chain management research has largely focused on monitoring as a self‐managed set of narrowly defined evaluative activities employed by firms to provide stakeholder accountability. Nevertheless, evidence is emerging that firms have developed a wide variety of monitoring systems in order to align with stakeholders’ expectations and leverage accountability to stakeholders. Drawing from the accounting literature, we synthesize a model that proposes how firms might address accountability for sustainability issues in their supply chain. At its core, the construct of sustainable evaluation and verification (SEV) captures three interrelated dimensions: inclusivity, scope, and disclosure. These dimensions characterize how supply chain processes might identify key measures, collect and process data, and finally, verify materiality, reliability and accuracy of any data and resulting information. As a result, the concept of monitoring is significantly extended, while also considering how different stakeholders can play diverse, active roles as metrics are established, audits are conducted, and information is validated. Also, several antecedents of SEV systems are explored. Finally, the means by which an SEV system can create a competitive advantage are investigated.